Regularity for double phase problems under additional integrability assumptions. (May 2020) - Ok, Jihoon
Abstract: We study the regularity of quasi-minimizers or minimizers of functionals of double phase type. In recent years, Baroni, Colombo and Mingione have investigated regularity theory for bounded minimizers in Baroni et al. (2015, 2018); Colombo and Mingione (2015) . In this paper, we assume the minimizers only belong to L γ -space.